Limited Value of KAI1/CD82 Protein Expression as a Prognostic Marker in Human Gastric Cancer. Issue 6 (21st May 2013) - Knoener, Maximilian; Krech, Till; Puls, Florian; Lehmann, Ulrich; Kreipe, Hans; Christgen, Matthias
Abstract : The cell surface glycoprotein KAI1/CD82 suppresses tumor growth and metastasis in animal models. This study aimed to evaluate the prognostic relevance of KAI1/CD82 protein expression in human gastric cancer. Primary gastric carcinomas ( n = 271) with amean clinical follow-up time of 48months were immunostained using the monoclonal anti-KAI1/CD82 antibody G2. Staining was evaluated as negative versus positive for statistical analysis. KAI1/CD82 immunoreactivity was absent in 103/271 (38%) cases. There was a trend towards KAI1/CD82 negativity in poorly differentiated cases ( p = 0.0679). Moreover, KAI1/CD82-negative carcinomas were associated with a higher pT status ( p = 0.0222), metastatic lymph node involvement ( p = 0.0018) and a higher clinical tumor stage ( p = 0.0050). The median overall survival times of KAI1/CD82-negative and KAI1/CD82-positive gastric carcinomas were 20 and 37 months, respectively ( p = 0.2305). These results are in line with the proposed function of KAI1/CD82 as a suppressor of tumor growth and metastasis. However, these data suggest that KAI1/CD82, as detected by immunohistochemistry, is of limited value as a prognostic marker for gastric cancer in routine histological workup.